Examining Speech Acts in Jordanian Advertising: Pragmatic Functions, Linguistic Features, and Rhetorical Devices - Rababah, Luqman (Journal of ethnic and cultural studies, 2023)
This qualitative study aims to investigate the persuasive speech acts used by Jordanian advertisers in fashion, food, and technology print advertisements. The selected advertisements were transcribed and analyzed using NVivo. Commercial speech acts were classified using Searle’s (1979) taxonomy of assertives, directives, commissives, expressives, and declaratives. The researcher took care to obtain the participants' informed consent and kept subject data confidential and anonymous. The evaluation of Jordanian advertising speech activities and the linguistic and cultural influences exerted upon them was conducted using tables and narratives. The findings of this research emphasize the diverse advertising strategies employed by Jordanian organizations. It was determined that directives, statements, and demands were the three most prevalent categories of speech acts in Jordanian advertising. These methods of communication were utilized to advocate for particular client actions, to make claims about the quality of the product being sold, and to guarantee certain outcomes for buyers. The study also revealed that Jordanian businesses frequently employ hyperbole, metaphor, and rhetorical queries in their marketing communications in order to make their products or services appear more desirable to potential consumers.